Comparative study of polystyrene/chemically modified wheat straw composite for green packaging application - Dixit S.; Yadav V.L. (My University, 2025)
The recalcitrant nature of native wheat straw (WS) biomass results from cellulose, lignin, hemicellulose and some amount of protein embedded together in a composite structure causing poor adhesion to a polymer matrix composite. Adequate pre-treatment can curtail the recalcitrance structure of WS and enhance the susceptible cellulose area to synthesize a green composite. This paper examined the effect of various chemical pre-treatment procedures in improving surface morphology of wheat straw. Moreover, polystyrene (PS), PS (60 wt%)/native WS (40 wt%), PS (60 wt%)/NaOH-treated WS (40 wt%), PS (60 wt%)/HCl-treated WS (40 wt%), and PS (60 wt%)/H2SO4-treated WS (40 wt%) composite films were prepared using solution casting method. The changes in crystalline structure, hydrophobicity, water vapor migration rate, and thermal and mechanical stabilities of synthesized bio-composites were examined. From the results it can be concluded that the alkali-treated WS is highly compatible with the PS and can be used to synthesize a biodegradable composite film for various industrial green packaging applications. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.